Determinants of self-rated health of Francophone seniors in a minority situation in Canada - Alimezelli, Hubert Tote; Leis, Anne; Karunanayake, Chandima; Denis, Wilfrid (Linguistic Minorites and Society / Minorités linguistiques et société, 2013)
Résumé La tendance actuelle montre que les institutions des services de santé et les gouvernements répondent de façon inadéquate aux besoins de plus en plus nombreux d’accès aux services de santé par les populations vieillissantes du Canada et d’autres pays développés. Après l’analyse de l’enquête post-censitaire 2006 de Statistiques Canada sur la Vitalité des Minorités de Langue Officielle, cette étude démontre qu’outre l’age, et en plus d’autres déterminants, les barrières linguistiques auxquelles font face les aînés de langue officielle en situation minoritaire affectent davantage l’autoévaluation de leur santé. Cette étude suggère quelques pistes de solution dont la compréhension des réalités contextuelles, l’amélioration de l’environnement linguistique et des services de santé dans la langue minoritaire. Mots-clés : déterminants de la santé, statut minoritaire, santé perçue, minorités linguistiques, aînés Abstract Current trends show that governments and health institutions in Canada and other developed nations are responding inadequately to the growing need for health services of the increasingly aging population. The Analysis of Statistics Canada’s 2006 post-census Survey on the Vitality of Official Language Minorities show that in addition to age and other socio-demographic determinants, linguistic barriers affect the self-rated health of seniors of official languages living in a minority situation. This study suggests among other things a greater understanding of Official language minorities’ contextual realities, the improvement of both the linguistic environment and services in the minority language. Keywords: health determinants, minority status, self-rated health, linguistic minorities, older adults

Diverging socioeconomic inequality in life expectancy of Francophones and Anglophones in Montréal, Québec: Tobacco to blame? - Auger, Nathalie; Harper, Sam; Barry, Amadou D. (Journal of Public Health: From Theory to Practice, 2013)
Aim We evaluated the ages and causes of death contributing to life expectancy gaps between economically advantaged and disadvantaged Francophones and Anglophones of Montréal, a Canadian metropolitan centre. Subject and Methods We partitioned the life expectancy gap at birth between socioeconomically disadvantaged and advantaged Francophones and Anglophones of Montréal (Québec) into age and cause of death components for two periods (1989–1993, 2002–2006). Changes in the contributions of causes over time were evaluated. Results Life expectancy was lower for disadvantaged Francophones and Anglophones by 5 years in men and 1.6 years in women compared with advantaged individuals. Over time, the socioeconomic gap widened for Francophones (men 0.3 years, women 2.8 years), due to smaller reductions in mortality from tobacco-related causes (cardiovascular, cancer, respiratory) in disadvantaged than in advantaged Francophones, especially after age ≥65 years (except lung cancer mortality that increased, particularly in disadvantaged women). The socioeconomic gap narrowed, however, for Anglophones (men 1.0 year, women 0.6 years), due to greater reductions in cardiovascular mortality in disadvantaged than advantaged Anglophones. Conclusion Socioeconomic inequalities in life expectancy decreased for Anglophones but increased for Francophones in Montréal due to underlying trends in tobacco-related mortality. Despite strong tobacco control laws in Canada, socioeconomic inequality in tobacco-related mortality is widening for Francophones in Montréal.

Contribution of local area deprivation to cultural-linguistic inequalities in foetal growth restriction: Trends over time in a Canadian metropolitan centre - Auger, Nathalie; Park, Alison L.; Daniel, Mark (Health & Place, 2013)
This study investigated temporal trends in heterogeneity of foetal growth restriction across neighbourhood deprivation levels for two culturally distinct communities (Anglophones and Francophones) in a North American metropolitan centre. Inequalities in foetal growth restriction related to deprivation fell from 1989 to 2008 for Francophones, but initial improvements for Anglophones later reversed with a rise in poor foetal growth in the most materially disadvantaged and, unexpectedly, advantaged areas as well. Inequalities in foetal growth restriction related to neighbourhood material deprivation may be emerging in this minority Anglophone population. Potential mechanisms underlying these trends are discussed, as well as implications for perinatal health policy.

Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

Suicide mortality gap between Francophones and Anglophones of Quebec, Canada - Burrows, Stephanie; Auger, Nathalie; Tamambang, Lum; Barry, Amadou. D. (Social psychiatry and psychiatric epidemiology, 2013)
Purpose Few studies evaluate language-group differences in suicide mortality. This study assessed the suicide mortality gap between Francophones and Anglophones of Quebec, Canada according to age, sex, method, region and socioeconomic deprivation. Methods Suicide decedents were extracted from the Quebec death file for 1989–2007 (N = 24,465). Age- and sex-specific suicide mortality rates were calculated for four periods (1989–1993, 1994–1998, 1999–2003, 2004–2007) for Francophones and Anglophones aged ≥10 years. Age-standardized rates of suicide by method, region, and level of social and material deprivation were calculated for each sex. Rate ratios and rate differences were estimated. Results Suicide rates for Francophones were two to three times higher than rates for Anglophones, and differences were greatest for adults aged 25–64 years. Francophone males had more than two times the rate of suicide by hanging or firearms than Anglophone males. Francophone females had twice the rate of hanging, poisoning or firearm suicide as Anglophone females, although precision was low. Francophone-Anglophone suicide mortality gaps were higher in urban areas despite lower suicide rates, and varied little across levels of social and material deprivation. Conclusions There was a large suicide mortality gap between Francophones and Anglophones of Quebec; especially, among adults aged 25–64 years.

Bien vieillir dans sa langue, sa culture et sa communauté. Soutien d’institutions fédérales clés et portrait des aînés anglophones du Québec - Commissariat aux langues officielles (Gouvernement du Canada, 2013)

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549 -X) - Lafrenière, Sylvie (Statistique Canada, 2013)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.

Lifestyle habits and health indicators of Québec Anglophones - Lussier, Marie-Hélène; Trempe, Normand (Institut national de santé publique du Québec, 2013)

Quelques habitudes de vie et indicateurs de santé des anglophones du Québec - Lussier, Marie-Hélène; Trempe, Normand (Institut national de santé publique du Québec, 2013)

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Enjoying your senior years in your own language, culture and community. Federal support from key institutions and a portrait of English-speaking seniors in Quebec - Office of the commissioner of official languages (Federal support from key institutions and a portrait of English-speaking seniors in Quebec, 2013)

Adaptation linguistique des soins et des services de santé : enjeux et stratégies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Language adaptation in health care and health services: Issues and strategies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)

Avoidable mortality of the two main linguistic communities in Québec. Language as a determinant of health status and service quality - Trempe, Normand; Diogo Barry, Amadou D.; Lussier, Marie-Hélène.; Lo, Ernest (Institut national de santé publique du Québec, 2013)

La mortalité évitable des deux principales communautés linguistiques du Québec. La langue, déterminant de l'état de santé et la qualité des services - Trempe, Normand; Diogo Barry, Amadou; Lussier, Marie-Hélène; Lo, Ernest (Institut national de santé publique du Québec, 2013)